2015
DOI: 10.1016/j.jff.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pepper (Zanthoxylum bungeanum Maxim.) leaf extract on the antioxidant enzyme activities of salted silver carp (Hypophthalmichthys molitrix) during processing

Abstract: A B S T R A C THere we investigated the lipid-protective effects of Chinese red pepper (Zanthoxylum bungeanum Maxim.) leaf (ZML) extract and chlorogenic acid, hyperoside, and quercitrin on salted fish during processing. ZML extract and the polyphenols expressed high total antioxidant capacity and DPPH free radical scavenging activity. Salted fish with the ZML extract had higher endogenous antioxidant enzyme (superoxide dismutase, catalase and glutathione peroxidase) activities, lower peroxide value (PV) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…This result was in accordance with a recent study in cooked ground pork (Juntachote et al, 2007), which showed the antioxidant activity of dried galangal powder and its ethanolic extract was likely due to curcuminoids. Therefore, ZML extract containing high levels of total phenolic constituents with its primary components of chlorogenic acid, hyperoside and quercitrin (Li et al, 2014;Yang et al, 2013) contributed to the retardation of lipid peroxidation and hence to gain low TBARS concentrations. Both in the dorsal and ventral muscle, the TBARS values of the treatments with higher amounts of ZML extract exhibited an increasing effect in retarding lipid oxidation.…”
Section: Changes Of Tbars Values During Processing Of Salted Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was in accordance with a recent study in cooked ground pork (Juntachote et al, 2007), which showed the antioxidant activity of dried galangal powder and its ethanolic extract was likely due to curcuminoids. Therefore, ZML extract containing high levels of total phenolic constituents with its primary components of chlorogenic acid, hyperoside and quercitrin (Li et al, 2014;Yang et al, 2013) contributed to the retardation of lipid peroxidation and hence to gain low TBARS concentrations. Both in the dorsal and ventral muscle, the TBARS values of the treatments with higher amounts of ZML extract exhibited an increasing effect in retarding lipid oxidation.…”
Section: Changes Of Tbars Values During Processing Of Salted Fishmentioning
confidence: 99%
“…The polyphenols in the pepper (Z. bungeanum Maxim.) leaf (ZML), which are usually discarded, were identified in our earlier study (Li, Wang, Li, & Peng, 2014;Yang, Li, Tan, & Jiang, 2013), and chlorogenic acid, hyperoside, and quercitin are the major bioactive compounds. There are several published reports about the application of these bioactive compounds and the antioxidant activity of the essential oil of the pericarps of pepper (Oliver-Bever, 1982;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In studies by our research team, F. sambucinum was observed to cause dry rot of Zanthoxylum bungeanum stems [22,23,24]. Z. bungeanum , also called “Huajiao” in China, is an economically important crop harvested as a food seasoning [25,26]. Dry rot of Z. bungeanum has caused great losses in the main producing provinces of China, especially in Shaanxi Province [24].…”
Section: Introductionmentioning
confidence: 99%
“…The peroxide value (PV) and the thiobarbituric acid reactive substances (TBARS) assay were performed as described by Li, Wang, Li, and Peng, (). The PV values were expressed as m mol/kg muscle, and the TBARS values were expressed as mg malonaldehyde (MDA)/kg dry muscle.…”
Section: Methodsmentioning
confidence: 99%